Random Attractors for Stochastic Three-Component Reversible Gray-Scott System with Multiplicative White Noise - Anhui Gu (Journal of Applied Mathematics)
The paper is devoted to proving the existence of a compact random attractor for the random dynamical system generated by stochastic three-component reversible Gray-Scott system with multiplicative white noise.